Key amino acid residues involved in mammalian and insecticidal activities of Magi4 and Hv1b, cysteine‑rich spider peptides from the δ‑atracotoxin family (2020)
ABSTRACT: δ-Atracotoxins, also known as δ-hexatoxins, are spider neurotoxic peptides, lethal to both vertebrates and insects. Their mechanism of action involves the binding to of the S3/S4 loop of the domain IV of the voltage-gated sodium channels (Nav). Because of the chemical difculties of synthesizing folded synthetic δ-atracotoxins correctly, here we explore an expression system that is designed to produce biologically active recombinant δ-atracotoxins, and a number of variants, in order to establish certain amino acids implicated in the pharmacophore of this lethal neurotoxin. In order to elucidate and verify which amino acid residues play a key role that is toxic to vertebrates and insects, amino acid substitutes were produced by aligning the primary structures of several lethal δ-atracotoxins with those of δ-atracotoxins-Hv1b; a member of the δ-atracotoxin family that has low impact on vertebrates and is not toxic to insects. Our fndings corroborate that the substitutions of the amino acid residue Y22 from δ-atracotoxin-Mg1a (Magi4) to K22 in δ-atracotoxin-Hv1b reduces its mammalian activity. Moreover, the substitutions of the amino acid residues Y22 and N26 from δ-atracotoxin-Mg1a (Magi4) to K22 and N26 in δ-atracotoxin-Hv1b reduces its insecticidal activity. Also, the basic residues K4 and R5 are important for keeping such insecticidal activity. Structural models suggest that such residues are clustered onto two bioactive surfaces, which share similar areas, previously reported as bioactive surfaces for scorpion α-toxins. Furthermore, these bioactive surfaces were also found to be similar to those found in related spider and anemone toxins, which afect the same Nav receptor, indicating that these motifs are important not only for scorpion but may be also for animal toxins that afect the S3/S4 loop of the domain IV of the Nav.